2022
DOI: 10.3390/jcm11123383
|View full text |Cite
|
Sign up to set email alerts
|

First 24-Hour Potassium Concentration and Variability and Association with Mortality in Patients Requiring Continuous Renal Replacement Therapy in Intensive Care Units: A Hospital-Based Retrospective Cohort Study

Abstract: Serum potassium (K+) levels between 3.5 and 5.0 mmol/L are considered safe for patients. The optimal serum K+ level for critically ill patients with acute kidney injury undergoing continuous renal replacement therapy (CRRT) remains unclear. This retrospective study investigated the association between ICU mortality and K+ levels and their variability. Patients aged >20 years with a minimum of two serum K+ levels recorded during CRRT who were admitted to the ICU in a tertiary hospital in central Taiwan betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Furthermore, the results revealed that a higher APACHE II score, potassium levels, lactate levels, sodium levels, and respiratory rate; multiple organ support use and medication use; and older age as well as lower SPO2, MAP, platelet count, BMI, and O2 saturation were positively correlated with in-hospital death. The findings regarding the importance of variables are consistent with those of a previous study [ 7 , 11 , 12 , 32 , 33 , 34 ]. In this study, an inverse relationship was noted between diabetes mellitus and in-hospital mortality.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the results revealed that a higher APACHE II score, potassium levels, lactate levels, sodium levels, and respiratory rate; multiple organ support use and medication use; and older age as well as lower SPO2, MAP, platelet count, BMI, and O2 saturation were positively correlated with in-hospital death. The findings regarding the importance of variables are consistent with those of a previous study [ 7 , 11 , 12 , 32 , 33 , 34 ]. In this study, an inverse relationship was noted between diabetes mellitus and in-hospital mortality.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, PNI, which measures albumin and lymphocytes, is a simple and effective method that can be used to assess nutritional status and predict outcomes in clinical settings.The study population was divided into two distinct groups based on the established median values of the PNI: low PNI (< 27.28) and high PNI (≥ 27.28).The demographic and clinical information of patients, including age, sex, BMI, Acute Physiology and Chronic Health Evaluation (APACHE) II score at ICU admission, diagnostic criteria for AKI, the timing of CRRT initiation, vital signs within 24 h of CRRT initiation, urine output, pre-CRRT medication, serum biochemical data, presence of comorbidities, and use of PN, was collected from the CCHRD. These clinical confounders have been discussed in previous articles [9,23].…”
mentioning
confidence: 96%
“…The demographic and clinical information of patients, including age, sex, BMI, Acute Physiology and Chronic Health Evaluation (APACHE) II score at ICU admission, diagnostic criteria for AKI, the timing of CRRT initiation, vital signs within 24 h of CRRT initiation, urine output, pre-CRRT medication, serum biochemical data, presence of comorbidities, and use of PN, was collected from the CCHRD. These clinical confounders have been discussed in previous articles [9,23].…”
mentioning
confidence: 96%